Synthesis and characterisation of polymer-anchored oxidovanadium(IV) complexes and their use for the oxidation of styrene and cumene - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (European Journal of Inorganic Chemistry, 2007)
{The Schiff bases H(2)fsal-ea (I), H(2)fsal-pa (II) and H(2)fsal-amp (III), derived from 3-formylsalicylic acid and 2-aminoethanol, 3-aminopropanol and 2-amino-2-methylpropanol, respectively, have been connected, by means of covalent bonds, to chloromethylated polystyrene cross-linked with 5% divinylbenzene. On treatment with [
Keywords: dissolution rate; mass transfer coefficient; particle size distribution; polydisperse solid; reactive liquid

Heat and mass transfer analysis in air gap membrane distillation process for desalination - Pangarkar, Bhausaheb L.; Sane, Mukund G. (Membrane Water Treatment, 2011)
The air gap membrane distillation (AGMD) process was applied for water desalination. The main objective of the present work was to study the heat and mass transfer mechanism of the process. The experiments were performed on a flat sheet module using aqueous NaCl solutions as a feed. The membrane employed was hydrophobic PTFE of pore size 0.22 mu m. A mathematical model is proposed to evaluate the membrane mass transfer coefficient, thermal boundary layers' heat transfer coefficients, membrane/liquid interface temperatures and the temperature polarization coefficients. The mass transfer model was validated by the experimentally and fitted well with the combined Knudsen and molecular diffusion mechanism. The mass transfer coefficient increased with an increase in feed bulk temperature. The experimental parameters such as, feed temperature, 313 to 333 K, feed velocity, 0.8 to 1.8 m/s (turbulent flow region) were analyzed. The permeation fluxes increased with feed temperature and velocity. The effect of feed bulk temperature on the boundary layers' heat transfer coefficients was shown and fairly discussed. The temperature polarization coefficient increased with feed velocity and decreased with temperature. The values obtained were 0.56 to 0.82, indicating the effective heat transfer of the system. The fouling was observed during the 90 h experimental run in the application of natural ground water and seawater. The time dependent fouling resistance can be added in the total transport resistance.
Keywords: AGMD; Desalination; heat transfer coefficient; mass transfer coefficient; temperature polarization coefficient

Solvent extraction of butanol from synthetic solution and fermentation broth: batch and continuous studies - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Gaikwad, Shashank G.; Chavan, V, Prakash; Bankar, Sandip B. (Separation and Purification Technology, 2020)
Product recovery is one of the essential finishing steps to any commercial fermentation process. In acetone-butanol-ethanol (ABE) fermentation, butanol recovery is quite tedious mainly due to dilute product and multiple byproduct formation in complex media. Among different recovery methods, extraction has attracted considerable attention in biofuel recovery owing to its high selectivity, low energy consumption, and ease of operation. In present work, the butanol extraction performance from synthetic solvent mixture containing ABE was tested in batch and continuous operations using 20% (v/v) decanol in oleyl alcohol. The optimized extraction conditions were then validated using actual fermentation broth to confirm effectiveness of the extraction operation. The distribution coefficient (K-d) and batch extraction efficiency (E) were in the range of 5.60-9.80 and 87.70-86.90% for fermentation broth and synthetic solution, respectively for a given initial concentration of butanol in the aqueous phase. Further, E was relatively improved by supplementing different inorganic salts. Sodium hydroxide (5%, w/v) was highly effective to recover butanol from fermentation broth (E similar to 97.70%) with K-d of 33.10. Besides, the continuous counter current extraction of butanol in a packed column was performed. The volumetric mass transfer coefficient (kLa) was estimated to be 0.025 1/min at an optimized superficial velocity of the aqueous phase (0.28 cm/min) and sodium hydroxide concentration (5%, w/v). Height of the extraction column was estimated to be 28.32 cm using height of transfer unit (HTU) and number of transfer unit (NTU) concept for extraction efficiency of 97.20%. Overall, the present study has demonstrated an enhanced extraction efficiency of butanol from fermentation broth.
Keywords: Biobutanol; Equilibrium stages; Height of transfer unit; liquid-liquid extraction; mass transfer coefficient; Number of transfer unit